Working together to develop interventions for young drivers, pre-crash, pre-offence, and pre-licence: A pilot multi-agency collaboration. (January 2019) - Scott-Parker, B.; Stokes, L.; Gardner, S.; Cawkwell, M.; Wilson, M.; Panoho, S.; Klump, S.
Highlights: Multi-agency collaboration for pilot multi-stage project to identify high risk young drivers (HRYD) Stage 1 literature review revealed profile of risky behaviours and personal characteristics. Stage 2 focus groups revealed driver characteristics, behaviours, and influencers. Stages 3, 4 refinement and testing model revealed four clusters of young driver offenders, including HRYD. Abstract: Background: Young drivers persist as a major public health problem due to their over-involvement in road crashes in which they and other road users are injured. In 2013 a multi-agency collaborative working group was created in the Sunshine Coast region of Queensland, Australia, to improve road safety more generally, and to improve young driver road safety specifically. Funding for a four-stage project was generated, with the aim of elucidating how to identify high risk young drivers (HRYD) – pre-offence, pre-crash – so that early intervention may prevent problematic on-road behaviour. This manuscript summarises the findings of the four-stage pilot project. Method: Stage 1 was a comprehensive literature review of profiling problematic youth (e.g., HRYD). Stage 2 operationalised focus groups with stakeholders. Stage 3 was the development of the HRYD model through the integration of the findings of Stages 1 and 2. Stage 4 was a two-step cluster analysis of de-identified police records of n = 2973 Sunshine Coast youth aged 17–25 years with offence data from the age of 14 years. Results: The HRYD model comprised on-road (e.g., offences) and off-road (e.g., community behaviour) behaviours/characteristics. Cluster analysis identified four groups: cluster 1 (21.4% of sample) and 3 (23.8%) comprised non-injury and injury crashers, cluster 2 (40.1%) comprised HRYD, cluster 4 (14.7%) comprised substance users. Discussion and implications: The multi-agency collaboration developed a HRYD model and tested it in a real-world sample of youth with road and non-road offences detected by police from the age of 14 years. The largest gains in the short-term relate to 'picking the low hanging fruit', with technology such as automated number plate recognition able to identify problematic youth, for example, through the detection of expired vehicle registration. Premised on the notion that 'prevention is better than the cure', the next project will test the veracity and robustness of the model in two populations in Queensland (one larger rural region, one large city region). The findings will inform the development, application, and evaluation of multi-agency interventions targeting young drivers more generally (e.g., non/injury crashers), potential substance-affected drivers (e.g., users of illicit drugs, alcohol), and potential HRYD before they offend, before they crash, and indeed before licensure.